Domestic Violence Among Iranian Women: A Systematic Review and Meta-Analysis - Hajnasiri, Hamideh (Iran Red Crescent Med J, 2016)
CONTEXT: Violence against women, or domestic violence, is both a physical and mental health issue that is rampant in many societies. It undermines the personal health of those involved by inflicting physical, sexual, and psychological damage. The purpose of the present systematic review and meta-analysis is to assess the prevalence of domestic violence in Iranian society. EVIDENCE ACQUISITION: A total of 31 articles published between 2000 and 2014 in Iranian and international databases (MagIran, IranMedex, SID, Google Scholar, Science Direct, PubMed, Pre Quest, and Scopus) were examined. The data collected from the articles were analyzed through a meta-analysis using a random effects model. The heterogeneity of the articles was examined using the I2 index, and the analyses were performed with STATA software version 11.2. RESULTS: Based on the 31 articles, which represent a sample size of 15,514 persons, we estimated the prevalence of domestic violence to be 66% (CI 95%: 55 - 77). The geographical classification showed that the prevalence of domestic violence was 70% (CI 95%: 57 - 84) in the east of the country, 70% in the south (CI 95%: 32 - 100), 75% in the west (CI 95%: 56 - 94), 62% in the north (CI 95%: 37 - 86), and 59% in the center (CI 95%: 44 - 74). CONCLUSIONS: The results of the study showed a high prevalence of domestic violence in Iran, which requires the adoption of appropriate measures and the initiation of effective interventions by the legal authorities. These measures and interventions should aim to determine the causes of domestic violence and to develop ways of controlling and reducing this destructive phenomenon.